Intra-operative difficulties in repeat caesarean section-in a tertiary care hospital - Singh, Neelima; ., Sreedevi; Lavanya, Bolle (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Caesarean section is associated with risks of postoperative adhesions, incisional hernias (which may require surgical correction) and wound infections. The risk of the surgery may be increased due to a number of factors. The aim of the study was to study the effects of repeated caesarean sections and intra surgical difficulties. Methods: A cross sectional, observational, hospital-based study was done for all patients with repeat caesarean section for a period of 8 months. 190 women who have undergone one or more caesarean section of term gestation with a live foetus irrespective of amniotic fluid colour and amount with cephalic, breech, or transverse presentation elective and emergency caesarean sections and singleton or multiple pregnancies were selected for study. Results: In the present study the highest prevalence of previous C-section was seen in age group 20-29 years, which accounted for (88.5%). Complications are present in 42.1% patients in which adhesions was the most found complication. Adhesion between Parietal peritoneum and anterior surface of uterus is present in 26.3% patients, omentum and uterus is present in 25.8% patients, adhesiolysis was done in 28.9% patients. 80% complications were present in patients with one previous CS. The association was found to be statistically significant. Conclusions: Women undergoing repeated cesarean sections have a risk of increased morbidity due to increased intraoperative complications. To avoid this one should keep the cesarean section rate at reasonable limit with appropriate surgical techniques and to limit primary cesarean section rate.